A five-year observational study of the patterns of neurological disorders among Yemeni patients based on magnetic resonance imaging - Aklan, Hameed M.; Ankarali, Handan; Alimoglu, Orhan (International Journal of Current Medical and Pharmaceutical Research, 2017)
Background: Neurological disorders are significant threats causing mortality and disability worldwide. In Yemen, there is a paucity of data on the pattern of these disorders. Thus, the present study was conducted on patients with suspected diagnosis of neurological disorders admitted to the University of Science and Technology Hospital to determine the prevalence and trend of neurological diseases. Methods: A total of 1850 patients with suspected diagnosis of neurological diagnosis were enrolled in this study. Biodata were retrieved from patient records. Patients were examined for neurological disorders using the magnetic resonance imaging. Results: The most common neurological disorders were infarction (7.9%, 95% CI: 7 - 9%), senile brain atrophy (7.8%, 95% CI: 7 - 9%) and multiple sclerosis (3.3%, 95% CI: 3 - 4%). A significant increase in ischemia (?2 = 11, p =0.001), senile brain atrophy (?2 = 162, p < 0.001), meningioma (?2 = 14, p <0.001), and infarction (?2 = 77.6, p < 0.001) with increase in age was noted. However, younger age showed a statistically significant association with arachnoid cysts (?2 = 20, p< 0.001) and atrophy (?2 = 8, p = 0.038).There were statistically significant differences between males and females regarding some neurological disorders as senile brain atrophy (?2 = 21, p < 0.001) and infarctions(?2 = 11, p = 0.001) were more common among males while pituitary macroadenomas were more common among females (?2 = 5, p = 0.021). In the last three years of the study period, there was a significant increase in the prevalence of multiple sclerosis and a decrease in that of infarction. Conclusion: In conclusion, infarction, senile brain atrophy and multiple sclerosis are the most frequent neurological disorders among Yemeni patients. This study warrants further multicenter studies to identify the possible predictors of these most frequent neurological disorders in Yemen.